Prevalence of Hypertension and its Associated Risk Factors Among Military Personnel of Nepali Army in Selected Military Barracks of Nepal - Budhathoki, Lee; Paudel, Leela; Shrestha, Bikal; Phuyal, Naveen; Bhandari, Ganesh; Shrestha, Kshitij Kumar; Khadka, Sagar; Shrestha, Lochana (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Hypertension is an important health issue among Military personnel because of their unique nature of duties and services. Unhealthy diet, low intake of fruits and vegetables, physical inactivity, harmful use of alcohol and tobacco, overweight or obesity, family history of hypertension are the risk factors for hypertension. This study aims to identify the prevalence and risk factors of hypertension among Military personnel of Nepal Army.Methods: Cross-sectional study was conducted among 416 serving army personnel posted at four selected military barracks; Dhading, Birgunj, Lamjung and Tanahun with the data collection period from January to June 2020. The civilian population working in Army units, retired army personnel and dependents were excluded from the study. Systematic random sampling was used for the selection of participants. Pre-tested questionnaires, weighing machine, stadiometer, measuring tape, stethoscope and BP set were used as a tool for data collection. Data was entered and analyzed using SPSS 20.0.Results: Participants had a mean age of 34.46 ± 5.25 years. Prevalence of hypertension and pre-hypertension was 13.4% and 37.3% respectively. Among the risk factors studied for hypertension; spouse’s education, tobacco chewing, history of hypertension in father and being overweight, were found to be statistically significant with p value of 0.047, 0.000, 0.021, and 0.002 respectively.Conclusions: Prevalence of hypertension was less in military personnel compared to other occupational groups. Avoidance of tobacco consumption, awareness on risk factors of non-communicable disease and maintenance of body weight by regular physical exercise could help reduce prevalence of hypertension in military personnel.